Studies on the antimicrobial potency of the marine algae - Caulerpa scalpelliformis and Spyridia species - Singh, Mrinalini (International Journal of Biological Research, 2014)
Objective: To study the antimicrobial potency of the marine algae – Caulerpa scalpelliformis and Spyridia sp. Methods: Caulerpa scalpelliformis and Spyridia sp. were screened for the presence of bioactive components by extracting them with suitable solvents and studying their antimicrobial activities against varied human pathogens. An attempt has also been made to separate the unknown compounds using Thin Layer Chromatography and purify the extracts using column chromatography since not much work has been carried out in these species. Results: In Spyridia, only the methanolic extract could produce zone of inhibition against Staphylococcus aureus and Salmonella sp. whereas in Caulerpa scalpelliformis, only the petroleum ether, chloroform and methanolic extracts showed antimicrobial properties. Better resolution was found in the mobile phase containing chloroform: methanol 80: 20 ratio for Caulerpa. Hence, its methanolic extract was fractioned in silica gel column and these fractions were effective against some of the test organ-isms but not against all. Conclusion: Further investigation is required to study the nature of compounds with antimicrobial properties with reference to Caulerpa scalpelliformis; whereas with Spyridia sp. the study can be extracted to collect the samples during different seasons of a year and confirm its antimicrobial potency. Keywords: Caulerpa Scalpelliformis, Spyridia SP, Antimicrobial Activities, Thin Layer Chromatography, Column Chromatography.